Penerapan Deep Back Massage (DBM) Terhadap Penurunan Nyeri Persalinan Kala I Fase Aktif : Literature Review - Ningsi, Tes Aprila (Jurnal Kesehatan & Disiplin Ilmu, 2025)
This study aims to analyze the effect of Deep Back Massage (DBM) on labor pain intensity in active phase I laboring mothers. Searching for research articles in several databases using certain keywords in the period 2020-2025. The search results obtained 74 articles using nursing interventions, only 44 articles met the inclusion criteria. The researcher assessed the 44 articles with Duffy's Research Appraisal Checklist Approach and obtained 11 articles including the superior paper category so that they were good for further analysis. Critical analysis of 11 articles was carried out based on design, population and sample, sampling, treatment, parameters, findings and conclusions. Results and discussion: 11 research articles that include one Randomized Controlled Trial (RCT) study, one qualitative study, and nine quasi-experimental studies, it can be concluded that Deep Back Massage (DBM) is effective in reducing the intensity of labor pain in active phase I laboring women. Conclusion and Suggestion: Deep Back Massage is a nonpharmacological method that is effective in reducing labor pain in the active phase of labor. This technique can be applied as a complementary intervention in midwifery practice to improve the comfort of laboring women.